2019
DOI: 10.1007/s10803-019-04012-1
|View full text |Cite
|
Sign up to set email alerts
|

Autism Mental Status Examination (AMSE): A Valid Instrument in the Evaluation of Pre-school Children with Suspected Autism Spectrum Disorders?

Abstract: In this study the Autism Mental Status Exam (AMSE) was validated towards ICD-10 Autism Spectrum Diagnoses (ASD) based on an interview with the Diagnostic Interview for Social and Communication Disorders (DISCO-11) with parent(s)/caregiver(s) in a group of 124 children referred for assessment to a clinical assessment unit for pre-school children. The results from the study indicates a Fair relation across the AMSE score and ICD-10 Autism Spectrum Disorder (ASD). AMSE mean score for childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
2
0
2
Order By: Relevance
“…The higher incidence found by Cravedi et al (14% vs. 8.9%) may be related to the cut-off of AMSE that was used to identify ASD children. Recently, Cederlund (2019) reported that AMSE is a valid instrument, but the optimal cut-off score for a probable diagnosis of ASD, according to ICD10 criteria, is 7 with a sensitivity and specificity of 75% and 78%, respectively [34].…”
Section: Discussionmentioning
confidence: 99%
“…The higher incidence found by Cravedi et al (14% vs. 8.9%) may be related to the cut-off of AMSE that was used to identify ASD children. Recently, Cederlund (2019) reported that AMSE is a valid instrument, but the optimal cut-off score for a probable diagnosis of ASD, according to ICD10 criteria, is 7 with a sensitivity and specificity of 75% and 78%, respectively [34].…”
Section: Discussionmentioning
confidence: 99%
“…A total score was calculated by adding the items together, resulting in a score between 0–14, where a threshold of ≥5 was used to indicate that symptoms were congruent with an autism diagnosis [ 40 ]. The AMSE has established internal consistency, inter-rater reliability, concurrent validity and diagnostic accuracy among young people on the spectrum [ 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Por otro lado, su aplicación está validada para niños de 16 a 30 meses. Con este objetivo se desarrolló el AMSE, que se basa en el registro de 8 ítems de signos que pueden ser observados y/o reportados, y tiene un mayor rango etario de aplicación 62 .…”
Section: Pruebas Específicas De Detección De Teaunclassified